A STUDY ON INFORMAL MARKET CLUSTER ACTIVITIES CONCENTRATING AROUND MENDI MARKET AREA: IS RELOCATION THE BEST OPTION? - Undiri Kima; Agung Sugiri (Diponegoro University, 2015)
The market provides a means of survival for the local and urban communities. The local farmers, local artisans, and other informal sectors find the market as their source of income and food and a place of relaxation. They find the market as a place where they meet friends. The article seeks to understand and analyze how informal sectors cluster groups agglomerate in and around the Mendi Local Market (LM) area of Papua New Guinea. This research has made particular reference to Street Vendors (SV) who are operating their daily activities in and along the market corridor and exert their influences to the LM and the public. The study provides the scenario to understand the impact of the social relations of the informal street vendors and their daily associated influences on LM. This article seeks to trace and to understand how informal market clusters are operating and concentrating around the local market. The conclusion suggests that the relationships of the informal sector, street vendors, and local market should be promoted through an appropriate inclusive policy and regulatory environment.The market provides a means of survival for the local and urban communities. The local farmers, local artisans, and other informal sectors find the market as their source of income and food and a place of relaxation. They find the market as a place where they meet friends. The article seeks to understand and analyze how informal sectors cluster groups agglomerate in and around the Mendi Local Market (LM) area of Papua New Guinea. This research has made particular reference to Street Vendors (SV) who are operating their daily activities in and along the market corridor and exert their influences to the LM and the public. The study provides the scenario to understand the impact of the social relations of the informal street vendors and their daily associated influences on LM. This article seeks to trace and to understand how informal market clusters are operating and concentrating around the local market. The conclusion suggests that the relationships of the informal sector, street vendors, and local market should be promoted through an appropriate inclusive policy and regulatory environment.